Evidence of Isotopic Fractionation During Vapor Exchange Between the Atmosphere and the Snow Surface in Greenland. Issue 6 (18th March 2019) - Madsen, M. V.; Steen‐Larsen, H. C.; Hörhold, M.; Box, J.; Berben, S. M. P.; Capron, E.; Faber, A.‐K.; Hubbard, A.; Jensen, M. F.; Jones, T. R.; Kipfstuhl, S.; Koldtoft, I.; et al.
Abstract: Several recent studies from both Greenland and Antarctica have reported significant changes in the water isotopic composition of near‐surface snow between precipitation events. These changes have been linked to isotopic exchange with atmospheric water vapor and sublimation‐induced fractionation, but the processes are poorly constrained by observations. Understanding and quantifying these processes are crucial to both the interpretation of ice core climate proxies and the formulation of isotope‐enabled general circulation models. Here, we present continuous measurements of the water isotopic composition in surface snow and atmospheric vapor together with near‐surface atmospheric turbulence and snow‐air latent and sensible heat fluxes, obtained at the East Greenland Ice‐Core Project drilling site in summer 2016. For two 4‐day‐long time periods, significant diurnal variations in atmospheric water isotopologues are observed. A model is developed to explore the impact of this variability on the surface snow isotopic composition. Our model suggests that the snow isotopic composition in the upper subcentimeter of the snow exhibits a diurnal variation with amplitudes in δ 18 O and δD of 2.5‰ and 13‰, respectively. As comparison, such changes correspond to 10–20% of the magnitude of seasonal changes in interior Greenland snow pack isotopes and of the change across a glacial‐interglacial transition. Importantly, our observation and model results suggest, that sublimation‐induced fractionation needs to be included in simulations of exchanges between the vapor and the snow surface on diurnal timescales during summer cloud‐free conditions in northeast Greenland. Key Points: Data show evidence of isotopic fractionation during vapor exchange between the snow surface and atmosphere Model simulations suggest diurnal variation in the snow surface isotopic composition We propose an enhanced effective isotopic exchange between the surface of the snow grain and its interior